Assessing the Potential of Livestock and Plantation Businesses in Several Lampung Regions - Ahmad Efendi; Prasetya Nugeraha; Maulana Agung Pratama; Diang Adistya; Winda Septiani; Suprihatin Ali; Fina Agus Suci Ningtias; Retno Yulita; Novita Andini; Komang Niko Yan; Lc Hsia Asri Lam’a Bourlyn (Iapa Proceedings Conference, 2022)
Farms and plantations have the potential to thrive in various Lampung locations, including Pesawaran, Pringsewu, South Lampung, Tulang Bawang, and Bandar Lampung city. Lampung Province has a reasonably significant and abundant potential for agricultural natural resources, including the potential for agricultural business development, as shown in the development of banana, corn, cassava, and oyster mushroom production. One of the manufacturers is Lampung Province. Poultry farming is one of the most popular enterprises in the livestock sector, because it can be started on a small size and scaled up to a large scale. Laiding hens, quail cultivation, ducks, and catfish farming are some of the livestock sub-key sector's commodities in Lampung Province. The goal of this research is to identify the potential of livestock and plantation businesses in various locations of Lampung, revenue and income, features of business feasibility, and whether or not business developments in these areas are practicable. This research method employs a quantitative description method. This survey activity employs a direct approach with observation and interview techniques as a data gathering instrument. The information gathered is both primary and secondary. Based on the findings of the identification of business opportunities in the livestock and plantation sectors conducted in various locations throughout Lampung, it can be concluded that all of the businesses studied in this study are viable to pursue in terms of BEP, ROI, R/C Ratio, and Payback Periods.